PENGARUH FAKTOR-FAKTOR KUALITAS KEHIDUPAN KERJA TERHADAP KOMITMEN ORGANISASI KARYAWAN - Dian Kartika Sari; Rini Fatmawati (Faculty of Social and Political Science, 2014)
Focus of this study is the effect of quality of work life factor (compensation, participation, supervision, career development, physical environment, workplace integration) in commitment organization. This research is a quantitative study using regretion and sample in this research is using cluster sampling.This research is using SPSS 16.0 for windows showed that the factor of quality of work life (compensation, participation, supervision, career development, physical environment, workplace integration) have positive effort with employee organizational commitment. The result data SPSS showed that the compensation has dominant factor coefficients t 3,691 and physical environment doesn 't have effect to employee organizational commitment with coefficients t 1.9'6. Based on the results research, company should give training appropriate to the competence and give opportunity employee to socialize in their physical environment.